From Expectations to Execution: Developing Dating SIM FMVs for Girls - Tony Wibowo; Clarita Clarita; Jackson Candra Dinata; Joshua Lucas Samudra; Jonathan Sukianto; Bayu Syahputra (Institut Bisnis dan Teknologi Indonesia, 2025)
This study explores the development of a Full Motion Video (FMV) dating simulation game designed for female players, emphasizing the integration of Indonesian cultural elements into the narrative and gameplay. The research adopts the Game Development Life Cycle (GDLC) framework, covering stages including scripting, casting, video production, editing, and implementation using Unity with C# and the FMV node systems. A qualitative approach was employed through market analysis and semi-structured interviews to examine player expectations in terms of enjoyment, fantasy, motivation, satisfaction, and their overall experience. The findings indicate that FMV dating simulations appeal to players because of their immersive realism, emotional engagement, and escapist qualities. Narrative depth and character development are key factors influencing long-term engagement. Furthermore, integrating Indonesian cultural values, aesthetics, and social contexts enhances player immersion and promotes cultural appreciation. This study demonstrates that culturally grounded FMV games function not only as entertainment media but also as a platform for cultural preservation and global cultural dissemination.